POVERTY REDUCTION EFFORTS THROUGH THE HOPE FAMILY PROGRAM (PKH) AT THE SOCIAL SERVICE OF BARRU DISTRICT - Musdalifa; M, A.Pananrangi; Hartina (Meraja journal, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal